2018
DOI: 10.15252/embr.201744884
|View full text |Cite
|
Sign up to set email alerts
|

The MYO6 interactome reveals adaptor complexes coordinating early endosome and cytoskeletal dynamics

Abstract: The intracellular functions of myosin motors requires a number of adaptor molecules, which control cargo attachment, but also fine‐tune motor activity in time and space. These motor–adaptor–cargo interactions are often weak, transient or highly regulated. To overcome these problems, we use a proximity labelling‐based proteomics strategy to map the interactome of the unique minus end‐directed actin motor MYO6. Detailed biochemical and functional analysis identified several distinct MYO6‐adaptor modules includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 60 publications
1
53
0
Order By: Relevance
“…Indeed, in vitro experiments using purified proteins have shown that two adaptor proteins such as TOM1 and NDP52 can bind simultaneously directly to the MYO6 ABD1 and the ABD2 . Interestingly, in situ proximity labelling of MYO6 NI CBD has indicated that the mutation of the RRL motif also leads to the loss of TOM1, and its partner TOLLIP . These results suggest that although the interaction between TOM1 and MYO6 occurs directly via the WWY motif, in vivo the binding between MYO6 and TOM1 may also be indirect via ubiquitin using the ubiquitin‐binding TOM1 VHS domain and the MYO6 MyUb domain.…”
Section: Myo6 Molecular Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in vitro experiments using purified proteins have shown that two adaptor proteins such as TOM1 and NDP52 can bind simultaneously directly to the MYO6 ABD1 and the ABD2 . Interestingly, in situ proximity labelling of MYO6 NI CBD has indicated that the mutation of the RRL motif also leads to the loss of TOM1, and its partner TOLLIP . These results suggest that although the interaction between TOM1 and MYO6 occurs directly via the WWY motif, in vivo the binding between MYO6 and TOM1 may also be indirect via ubiquitin using the ubiquitin‐binding TOM1 VHS domain and the MYO6 MyUb domain.…”
Section: Myo6 Molecular Interactionsmentioning
confidence: 99%
“…Point mutations of the tryptophan of either binding motif, W 1202 of WWY or W 1262 of IWE, disrupt Dab2 binding to MYO6 and abolish cellular localization to clathrin-coated structures at the plasma membrane in vivo [52,76]. The importance of site I was confirmed by in situ proximity labelling, which demonstrated the loss of Dab2 and other proteins associated with clathrin-mediated endocytosis upon mutation of the WWY site [18].…”
Section: Myo6-adaptor Interaction At the Wwy-binding Motifmentioning
confidence: 99%
“…GFP-OPTN E50K and E478G pLXIN mutants were generated by site-directed mutagenesis. The myc-BirA*-OPTN pLXIN vector was created by subcloning OPTN into the myc-BirA* pLXIN plasmid described previously [55]. using the Δ Δ Ct method [57].…”
Section: Antibodies Plasmids and Reagentsmentioning
confidence: 99%
“…48 hours post-transfection, cells were lysed with 1% NP-40 lysis buffer (50 mM Tris-HCl pH 7.5, 150 mM NaCl, 1 mM EDTA, 1% NP-40) containing complete protease inhibitor cocktail (Roche), passed repeatedly through a 25G needle to homogenise and clarified by centrifugation at 20,000 x g for 10 minutes at 4°C. Subsequently, clarified lysates were incubated with 10 µl of GFP-nanobody Affi-gel resin [55] for 3 hours with mixing. Beads were washed with 1% NP-40 buffer, then TBS and were eluted in SDS sample loading buffer at 95°C.…”
Section: Immunoprecipitationmentioning
confidence: 99%
See 1 more Smart Citation